Influence of anatomical features in the endodontic treatment planning of maxillary anterior teeth - Jardel Francisco MAZZI-CHAVES; Graziela Bianchi LEONI; Juliana Santos OLIVEIRA; Yara Terezinha Corrêa SILVA-SOUSA; Ricardo Gariba SILVA; Ruben PAUWELS; Manoel Damião SOUSA-NETO (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study evaluate the maxillary anterior teeth anatomy by micro-computed tomography (μCT), about relevant characteristic for endodontic treatment planning. Fifty maxillary central incisors (MCI), lateral incisors (MLI) and maxillary canines (MC) were scanned using a μCT device. Two and three-dimensional parameters at 1 to 5mm distance to the apical foramen, external anatomic characteristics of the teeth and qualitative analysis of the internal anatomy was performed. The roundness and form factor values revealed a circular canal in the apical third in the MCI and MC, whereas MLI showed flattening in the apical third. The linear regression test indicated a progressive increase in the major/minor diameters in the five mm assessed (p < 0.001). The 3D analysis revealed the greatest volume and surface area in MC. The SMI showed a cylindrical geometry of root canals. All teeth presented Vertucci's type I root canal configuration. A mild curvature was prevalent in the MCI (45%) and a moderate one in the MLI (50%) and MC (50%). Palatal shoulder volume was smaller in the MLI (11.46 ± 3.09) than in the MCI (14.15 ± 3.85) and MC (13.95 ± 2.55). The most common exit of main apical foramen was in a central (22%), distolingual (30%) and mesiobuccal position (28%) for MCI, MLI and MC, respectively. Radicular grooves were observed in 2% of MCI and 4% of MLI. Two and three-dimensional data obtained by μCT allowed to observe morphological characteristics of internal/external anatomy of the maxillary anterior teeth. These characteristics may affect the endodontic treatment planning.